Brief survey on organometalated antibacterial drugs and metal-based materials with antibacterial activity. Issue 2 (26th January 2021) - Biegański, Przemysław; Szczupak, Łukasz; Arruebo, Manuel; Kowalski, Konrad
Abstract : Recent developments in the field of organometalated antibacterial drugs and metal-based materials with antibacterial activity are reviewed. They emerge as attractive candidates for combating pathogenic bacteria including drug resistant strains. Abstract : Rising bacterial antibiotic resistance is a global threat. To deal with it, new antibacterial agents and antiseptic materials need to be developed. One alternative in this quest is the organometallic derivatization of well-established antibacterial drugs and also the fabrication of advanced metal-based materials having antibacterial properties. Metal-based agents and materials often show new modes of antimicrobial action which enable them to overcome drug resistance in pathogenic bacterial strains. This review summarizes recent (2017–2020) progress in the field of organometallic-derived antibacterial drugs and metal-based materials having antibacterial activity. Specifically, it covers organometallic derivatives of antibacterial drugs including β-lactams, ciprofloxacin, isoniazid, trimethoprim, sulfadoxine, sulfamethoxazole, and ethambutol as well as non-antibacterial drugs like metformin, phenformin and aspirin. Recent advances and reported clinical trials in the use of metal-based nanomaterials as antibiofouling coatings on medical devices, as photocatalytic agents in indoor air pollutant control, and also as photodynamic/photothermal antimicrobial agents are also summarized.